Stock composition and ocean spatial distribution inference from California recreational Chinook salmon fisheries using genetic stock identification - Satterthwaite, William H. (2015)
We apply genetic stock identification (GSI) data and models of the catch and sampling process to describe spatial and temporal patterns in the stock composition and stock-specific catch-per-unit-effort (CPUE) of both tagged and untagged stocks encountered in California recreational ocean Chinook salmon fisheries during the period 1998-2002. Spatial and temporal distributions inferred from GSI sampling of stocks with tagged hatchery components were broadly consistent with those previously inferred from studies of tag recoveries alone, while GSI provided additional insight into untagged stocks of conservation concern. The catch in all times and areas was dominated (typically ≥90%) by the "Central Valley Fall" genetic reporting group, which is comprised primarily of Sacramento River fall run Chinook. Other contributing stocks were more spread out in space and time with the exception of Central Valley winter run Chinook, which were rarely encountered by boats fishing in port areas north of Point Reyes. Localized stock-specific CPUE appeared to increase near a stock's respective natal river while decreasing in other port areas at the time of adult return to freshwater for spawning. We describe methods for quantifying uncertainty in stock proportions, stock-specific catch, and determining the statistical support for proposed management boundaries hypothesized to represent "break points" in the spatial distributions for stocks of concern, and find at most equivocal support for a proposed delineation line at Point Reyes in north-central California.